Thermally responsive ionic liquids and polymeric ionic liquids : emerging trends and possibilities - Gupta, Nupur (2020)
Ionic liquid (IL) including polymeric ionic liquid (PIL) is a rapidly growing and widely research area due to its unique properties such as non-volatility, high ionic conductivity, electrochemical stability, and solvation potential. This focused review covers the advancement of thermally responsive ILs/PILs for applications, in which their osmotic potential and reversible interactions are exploited for water treatment and energy conversion through osmotically driven membrane processes and energy-saving smart windows. Our goal is to survey the recent key developments by highlighting the opportunities and challenges in this emerging and exciting field.